Core-Shell Structured Magnetite-Poly(diphenylamine) Microspheres and Their Tunable Dual Response under Magnetic and Electric Fields - Dong, Yu Zhen (Langmuir : the ACS journal of surfaces and colloids, 2021)
Core-shell type poly(diphenylamine)-coated magnetite (Fe3O4-PDPA) microspheres were designed and adopted as a novel actively tunable smart material which is responsive under both electric and magnetic fields. Their morphology, chemical structure, crystalline structure, and thermal properties were characterized using scanning electron microscopy, transmission electron microscope, Fourier transform-infrared spectroscopy, X-ray diffraction, and a thermal gravimetric analyzer. Their magnetic and dielectric properties were determined using vibrating-sample magnetometer and an LCR meter, respectively. They were dispersed in silicone oil and their electrorheological (ER) and magnetorheological (MR) responses under the electric and magnetic fields, respectively, were examined. The formation of chain structure of Fe3O4-PDPA based E/MR fluid under the application of electric field or magnetic field was observed by an optical microscopy and the sedimentation stability was observed by a Turbiscan optical analyzer system. It was observed that the yield stress, ER efficiency, and leakage current density increased with an increase in the particle concentration, while the slope of the electric field-dependent yield stress decreased. Several models such as the Bingham model, Herschel-Bulkley model, and Cho-Choi-Jhon equations were used to describe the shear stress curves of the ER fluid; the curves fitted well. For the dielectric properties, the two types of ER fluids tested displayed the same relaxation time and distribution; however, the one with the higher concentration had a higher dielectric constant and polarizability. The Fe3O4-PDPA based MR fluid (10 vol %) exhibited typical MR properties. In addition, the Herschel-Bulkley model matched well with the shear stress curves under a magnetic field